(untitled) - Kromkowski, John A. (New York, 2002)
Race and ethnic relations: American and global perspectives, explores race and ethnic relations in a global context, while extensively covering groups and issues in the United States. The text’s unique comparative approach is increasingly important and relevant in light of the growing ethnic diversity in a variety of societies, as well as the prominence of ethnic conflicts throughout the world.
Keywords: Race relations,Culture conflict; Periodicals,Ceriodicals; United States